EFFECTIVENESS OF COUNSELING IN INCREASING MOTHER'S KNOWLEDGE ABOUT STIMULATION LI.15 (JIANYU) TO OVERCOME MOTOR DISORDERS IN CHILDREN AT ATMA HOME CARE: EFEKTIFITAS PENYULUHAN DALAM MENINGKATKAN PENGETAHUAN IBU TENTANG STIMULASI LI.15 (JIANYU) UNTUK MENGATASI GANGGUAN MOTORIK PADA ANAK DI ATMA HOME CARE - Patemah (LPPM Widyagama Husada Malang, 2024)
Introduction. Knowledge is the process of turning things you don't know into knowing, from not getting to getting it. Stimulation is an activity to provide stimulation to children to optimize their motoric growth and development. From the results of a preliminary study carried out in August 2023 at Atma Home Care in Karanganyar village, Kec. Poncokusumo District. Malang, through interviews with 5 mothers who have 3 year old children, found that 20% only knew about LI.15 (Jianyu) stimulation and 70% had never known about LI.15 (Jianyu) stimulation. Objective. The aim of this research was to determine the mother's level of knowledge about LI.15 (Jianyu) stimulation. The research method uses a descriptive research design, namely only describing the mother's level of knowledge about LI.15 (Jianyu) stimulation in children. The research subjects were mothers of toddlers with children aged 2 years to 6 years who met the inclusion and exclusion criteria. The research sample size was 25 people. The research instrument is using a questionnaire. Data analysis uses distribution tables in the form of percentages. Results. The results of the research after the counseling activity were that the mother's knowledge about LI.15 (Jianyu) stimulation was at a good level of 72%, at an understanding level with good results was 64%, and the application level was found to be good at 56%. Conclusion. The conclusion of the research is that there is an increase in mothers' knowledge about LI.15 (Jianyu) stimulation in children with the hope that mothers will actively provide stimulation independently and attend Atma Home Care to take part in counseling activities.